Ivory Vikings : the mystery of the most famous chessmen in the world and the woman who made them - Brown, Nancy Marie (St. Martin's Press, 2015)
In the early 1800's, on a Hebridean beach in Scotland, the sea exposed an ancient treasure cache: 93 chessmen carved from walrus ivory. Norse netsuke, each face individual, each full of quirks, the Lewis Chessmen are probably the most famous chess pieces in the world. Who carved them? Where? Brown explores these mysteries by connecting medieval Icelandic sagas with modern archaeology, art history, forensics, and the history of board games.